2020
DOI: 10.1177/0021998320972462
|View full text |Cite
|
Sign up to set email alerts
|

The role of hybridisation and fibre architecture on the post-impact flexural behaviour of composite laminates

Abstract: Advanced composite materials are widely used in civil and military applications due to their superior specific strength and stiffness. However, they are susceptible to damage during impact loading. In order to improve the impact performance, yarn hybridisation and fibre architecture have been investigated in this study in order to evaluate their influence on the damage tolerance (i.e. post- impact flexural strength) of glass composite laminates. Two types of yarn have been used here, namely, pure glass yarns a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The open curves noticeable in the load-deformation graphs (Fig. 3, 5 and 7) of the samples prove that the striker has fully penetrated the samples, that is, full penetration has occurred [32]. This full penetration can also be noticed in damage patterns shown in Fig.…”
Section: Drop-weight Impact Resistance Test Resultsmentioning
confidence: 52%
“…The open curves noticeable in the load-deformation graphs (Fig. 3, 5 and 7) of the samples prove that the striker has fully penetrated the samples, that is, full penetration has occurred [32]. This full penetration can also be noticed in damage patterns shown in Fig.…”
Section: Drop-weight Impact Resistance Test Resultsmentioning
confidence: 52%
“…[12][13][14] Hence, it is important to understand their ability to continue functioning properly after damage events by evaluating their residual strength either compressive or flexural strength after impact tests. [15][16][17][18] Many investigations have demonstrated that the damage tolerance of composite laminates can be improved by adopting different strategies. One of the promising strategies is toughening of the polymer matrix by tuning the polymer chemistry or by incorporating different particles like rubbers, thermoplastics or nano-scale particles.…”
Section: Introductionmentioning
confidence: 99%
“…epoxy resin), offers the opportunity for the researchers to enhance the fracture toughness, impact resistance and also to explore the kinetic energy dissipation of these laminates during impact event. 10,[39][40][41] Ramirez et al 42 studied the effect of polyphenylene sulphide non-woven veils on mode-I and mode-II interlaminar fracture toughness of the unidirectional CF/EP laminates. Lee et al 43 investigated the behaviour of the mode-II interlaminar fracture toughness of carbon composite laminates by hybridising carbon fibre with nonwoven tissue (NWT).…”
Section: Introductionmentioning
confidence: 99%
“…13 Nevertheless, these laminates are particularly prone against delamination, which strongly reduces their properties such as the load-bearing capacity, compression strength, toughness, and fatigue life. 412 Therefore, the study to enhance the interlaminar fracture toughness of glass fibre laminates has drawn the attention of the designers and composites manufacturers. Delamination or inter-ply separation is the most predominant and crucial failure mechanism in composite laminates.…”
Section: Introductionmentioning
confidence: 99%